Analysing EFL learners’ problems to perform writing tasks: A case study of fourth form pupils at college Konan of Yamoussoukro (Côte d’Ivoire) - Kouassi Kouassi Théodore (Pensées Genre, Penser Autrement)
This work aims to analyse the problems of 3e pupils at Collège Konan of yamoussoukro dealing with writing tasks. To reach this objective, a survey has been carried towards 04 teachers and 100 pupils through some questionnaires. The results have revealed that the main causes to this phenomenon are: the incapability of the students to read the instructions, lack of learning materials, problem to understand the tasks. The findings also indicated other factors such as large classes, lack of total engagement of the learners, the non-mastery of writing teaching process by teachers.